Conversion of methyl carlactonoate to heliolactone in sunflower. Issue 9 (3rd May 2022) - Wakabayashi, Takatoshi; Shinde, Hikaru; Shiotani, Nanami; Yamamoto, Shunya; Mizutani, Masaharu; Takikawa, Hirosato; Sugimoto, Yukihiro
Abstract: Heliolactone is a non-canonical strigolactone isolated from sunflower root exudates. We have previously demonstrated that exogenously administered carlactonoic acid (CLA) was converted to heliolactone in sunflower. The conversion of CLA to heliolactone requires the methyl esterification of the carboxylic acid at C-19. Also, the CLA conversion to its methyl ester, methyl carlactonoate (MeCLA), was demonstrated by feeding experiment in sunflower. However, the involvement of MeCLA in heliolactone biosynthesis remains unclear. We synthesised MeCLA in its racemic form and resolved it into its enantiomers. Feeding experiments revealed that (11 R )-MeCLA was exclusively converted to heliolactone in sunflower. This result is an evidence that (11 R )-MeCLA is the biosynthetic precursor of heliolactone. Further conversion of heliolactone to an unidentified metabolite with a molecular mass larger than heliolactone by 16 Da was confirmed. The conversion was inhibited by a cytochrome P450 inhibitor, suggesting the involvement of cytochrome P450-dependent monooxygenation. Graphical Abstract: